Hardy Process Solutions : lots of data, but little insight - Griffy-Brown, Charla; Shanahan, Doreen E. ([London] : SAGE, 2016)
Hardy Process Solutions new General Manager, Chris Prazak, was caught off guard when sales declined precipitously after several month-over-month increases. While the company was capturing transactional data, Hardy business analysts had been unable to forecast sales beyond one week. The company had been hovering at about a 30% conversion rate on its sales leads. Prazak believed many qualified leads were not being nurtured effectively through the sales funnel. However, with very little automation supporting their sales processes, he had no way to really know. As Prazak pondered this problem, he realized it was much larger than simply acquiring a more robust CRM. This case study examines this topic.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Information technology -- Management -- Case studies; Information storage and retrieval systems -- Business -- Case studies